Plan de negocios para la creación de una pizzería buffet temática en Quito - Oleas Cazorla, Ariana Cristina (2016)
The business plan for the creation of a thematic pizzeria in the city of Quito, is a result of considering that today food and beverages establishments have concepts that have been modified from traditional to new trends, taking into account that the requirements of the customers are different, aware of their expectations and at the same time to satisfy their needs. The goal developing this project is to find the viability of this idea, that incentive the interest of people and at the same time creates high expectations of receiving a good service and product, and for the author of this investigation to ratify that it will provide positive results and conclusions. To get the final results and conclusions already mentioned, we will apply a process where the market investigation is focused on the tastes and needs of customers, reaching them through surveys and interviews that shows the reality of the market and the later analysis of it. The action plan presents guidelines that are developed in the administrative part and the strategies that are going to be adopted and accomplished in accordance to the objectives of the project and also identified the internal and external aspects that can affect or benefit this proposal. The main characteristics of the products offered are going to provide the advantage and value of the company, which will differentiate towards competition. The investment for the project, the monetary results, profits and the recovery of the investment mentioned, will be analyzed in a complete financial study that will reflect each category involved and the real value that the business would have. All these aspects mentioned in a general way, are going to be developed and studied in the research presented in this project